Desenvolvimento inicial de Moringa oleifera Lam. sob condições de estresse - Santos, Allívia Rouse Ferreira dos (2010)
Moringa (Moringa oleifera Lam.) belongs to the Moringaceae family and has several uses for family farms, mainly in water purification. However, there is little knowledge about the behavior of their seeds under stress conditions, which occurs under soils in northeastern region. The objective of this study was determine the Imbibition curve, and evaluate the water restriction, salinity, and pre-soaking of seeds in order to evaluate the initial development of Moringa oleifera. For the Imbibition curve, the weight of seeds was determined at every 4 hours. For water restriction induction were used different osmotic potentials (0, -0.1, -0.3, -0.4 and -0.6 MPa) obtained through the use of solutions of polyethylene glycol (PEG - 6000). For salinity tests there were used the solutions of sodium chloride at 5 concentrations (0, 25, 50, 100, 200 and 250 mol.m-3). For pre-soaking was employed two seed batches, using a non storage seeds and other batch with three-months storage at cold chamber. The pre-soaking seeds with distilled water were evaluated to assess the overcoming stress. For each treatment, was used a completely randomized design with four replications. For germination the seeds were placed in germination chamber, type BOD at 25ºC and continuous light and evaluated every 48 hours. For all tests (except for imbibitions curve) was evaluated the percentage, the speed germination index, time and average of speed germination, length and dry matter of root, hypocotyls and the whole seedling. The moringa seed needs 0.2 grams of water in a period of 128 hours to germinate. The germination of M. oleifera is possible under water restriction until -0.3 MPa, above this level is critical for germination and seedling development. The water pre-soaking with moringa seeds for 24 hours is effective for promoting lower pperiod to begin the germination. Vigor and germination of moringa seeds are inversely proportional to salt concentration, being affected when they are submitted to levels equal to or higher than 100 mol.m-3. Seeds water pre-soaking for 24 hours is effective to promote the reduction of the time necessary to initiate of the seeds germination, for seeds with